(untitled) (Revista Contexto & Saúde, 2025)
Objective: This study aimed to evaluate the presence of depressive symptoms in pregnant women who underwent prenatal care at the Family Health Strategy Units (ESF) in the municipality of Tubarão/SC, from August to December 2022. Method: This is an observational epidemiological study with a cross-sectional design, carried out with pregnant, primiparous or multiparous women with gestational age above 27 weeks who agreed to participate in the study and underwent prenatal care in the city of Tubarão/SC. The researchers elaborated a protocol for data collection and the depressive symptomatology was evaluated using the Edinburgh Postpartum Depression Scale (EPDS), a validated and self-administered instrument. For the association between the variables of interest, Pearson’s Chi -Square or Fisher’s Exact test was used and the pre-established confidence interval was 5%, p ≤ 0.05. Results: There was a prevalence of depressive symptoms in 25% of the evaluated pregnant women. There was an association between the EPDS instrument and: ethnicity, education, family income and planned pregnancy. Non-Caucasian pregnant women had a higher occurrence of depressive symptoms, as well as those with less education, low income and those who had not planned the pregnancy. Conclusions: In view of the prevalence of depressive symptoms found among the interviewees, the importance of the priority role of the Family Health Strategy (ESF) teams in minimizing the vulnerability of women in the peripartum period is evident.